Strategi Naratif dan Resistensi terhadap Konstruksi Identitas Agama dalam Novel Anjing Mengeong Kucing Menggonggong Karya Eka Kurniawan - Dewi Lenggani Prima Rini; Muhamad Adji; Mochamad Irfan Hidayatullah (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
In studies of contemporary Indonesian literature, Eka Kurniawan's novel Anjing Mengeong Kucing Menggonggong has primarily been examined through the lenses of internal conflict and power relations. However, few studies have positioned narrative strategy as the primary medium through which the negotiation of religious identity is represented. This study aims to examine how religious identity is represented in the novel and how narrative strategies are employed to portray resistance as part of the ongoing negotiation of identity. The analysis draws on Genette's narratology, focusing on order, duration, frequency, focalization, and is supported by Hall's theory of identity, Bell's theory of ritual, and Scott's concept of resistance. The findings show that religious practices such as prayer, Qur'an recitation, fasting, and circumcision are understood not only as acts of worship but also as practices that shape the characters' everyday lives. This subversive tendency is already suggested in the title (Dogs Bark, Cats Meow), which reverses what is commonly perceived as natural, creating space to question identities and norms that have long been accepted as fixed. The study also finds that narrative strategies play a significant role in constructing this representation through the use of temporal structure, focalization, and voice, allowing religiosity to be understood as a plural and evolving experience rather than a singular one. In the novel, resistance is not presented simply as a rejection of religious identity but as a way for the characters to reinterpret, negotiate, and reshape their religious identities through everyday experiences. Thus, the novel portrays religiosity as a dynamic space of identity negotiation that continues to evolve through the characters' lived experiences, social relationships, and personal choices.